Bundo Kanduang Monument in The Nagari Sijunjung Traditional Village, Sijunjung Regency, Form And Color Study - Kamel, Genta Fransisma; Rian, Rica; Hamzah, Hamzah; Suryanti, Suryanti (Institut Seni Indonesia Padang Panjang, 2025)
This research discusses the Bundo Kanduang Monument in the Nagari Sijunjung traditional village, Sijunjung Regency. According to the KBBI (Kamus Besar Bahasa Indonesia), a monument is a large and tall pillar made of stone, brick and so on. In another sense, a monument can also be a symbol/icon of the area concerned. This research includes a brief history, shape and colour. This research uses a qualitative approach which includes observation, interviews and literature study. The data used includes primary and secondary data. This research was carried out directly in the field, namely in Nagari Sijunjung, Sijunjung Regency, West Sumatra Province. Based on the results of this research, it shows that Nagari Sijunjung has a strong culture and customs. The existence of traditions and harmony among the people of Nagari Sijunjung is reflected in how they preserve their culture. Bundo Kanduang plays an important role in preserving culture and customs. With the existence of the Bundo Kanduang institution in Nagari Sijunjung, the deliberation and planning process for activities in Nagari Sijunjung runs smoothly. The shape of the Bundo Kanduang monument is a visual of Bundo Kanduang holding a carano on his head, telling how Bundo Kanduang is proof of the high status of women in Minangkabau. How do women and men have the same rights, and no one is superior to men or women in Minangkabau, because everyone has the right to express their own opinions. The colours on the monument illustrate that the characteristics possessed by Bundo Kanduang represent leadership, responsibility, fairness and wisdom.